Victim Power: A Clinical and Philosophical Paradox. (22nd September 2015) - Freeman, David
Abstract: This article is a personal attempt to understand the Holocaust and the inevitable question of "Why evil?" It draws upon personal experiences of the writer and suggests some possible religious and psychological understanding of the politics of the present state of Israel. Copyright © 2015 John Wiley & Sons, Ltd.